Judicial Development and the Institution of Arbitration in Comparative Analysis: Case Studies of Selected Countries - Shabani, Payam; Habibi Dargah, Behnam; Eslamipanah, Ali; Khaleghiyan, Javad (Legal Studies in Digital Age, 2025)
Judicial development is considered one of the fundamental prerequisites for achieving efficient and sustainable justice in contemporary legal systems. One of the key components in this process is the utilization of alternative dispute resolution methods, particularly arbitration, which can complement the judiciary by reducing case loads, enhancing the speed of proceedings, and increasing public satisfaction with the justice system. This article aims to investigate the relationship between judicial development and the institution of arbitration through a comparative analysis of the policies and structures in four countries: Iran, France, Singapore, and India. The primary research question is: What is the connection between judicial development policies and the institutional position of arbitration in these countries, and which models could be effective for reforming the justice system in Iran? The study employs a qualitative and comparative methodology, with data collected through the analysis of documents, laws, statistics, and previous studies. The findings suggest that in legal systems where arbitration is integrated into overall judicial policy, it has played a significant role in facilitating judicial development. In this context, the strategic use of arbitration capacities, alongside legislative and institutional reforms, is deemed a prerequisite for judicial development in countries such as Iran.